Rationale, design, and endpoints of the 'DEvice-Detected CArdiac Tachyarrhythmic Events and Sleep-disordered Breathing (DEDiCATES)' study: Prospective multicenter observational study of device-detected tachyarrhythmia and sleep-disordered breathing. (1st April 2019) - Gwag, Hye Bin; Park, Youngjun; Lee, Seong Soo; Kim, June Soo; Park, Kyoung-Min; On, Young Keun; Lee, Dae In; Shin, Dong-Gu; Choi, Eue-Keun; Kang, Gu-Hyun; Park, Hyoung-Seob; Park, Hyung Wook; et al.
Abstract: Background: Few studies have investigated the prognostic value of cardiac implantable electronic device (CIED)-detection of sleep-disordered breathing (SDB) for risk stratification of cardiovascular events. In the Device-Detected CArdiac Tachyarrhythmic events and Sleep-disordered breathing (DEDiCATES) study, we aim to determine whether device-detected SDB events are associated with increased risk of cardiac arrhythmias or other cardiovascular outcomes. Methods and design: Six-hundred patients (300 patients with low-voltage pacing devices and 300 with high-voltage defibrillator devices) who have dual chamber CIEDs with AP Scan™ function (Boston Scientific Inc., Marlborough, MA, USA) are planned to be enrolled in this study. AP Scan reports the average number of sleep disturbance events per hour per night in the form of a Respiratory Disturbance Index (RDI). The daily RDI values are to be used for quantitative measurement of the severity and burden of SDB. CIED-detected atrial high rate episodes (AHREs) and clinical atrial tachyarrhythmia will be assessed as the primary outcomes over a follow-up period of 2 years. Correlations between CIED-detected SDB and AHRE burdens will be analyzed. The secondary outcomes are CIED-detected or clinical ventricular arrhythmic events, stroke, heart failure hospitalization, mortality, and quality of life. Conclusion: This study will determine the prognostic value of automated diagnostic function of CIED for SDB, which will help to improve the cardiovascular prognoses of CIED patients by enabling convenient and accurate assessments of SDB events. Highlights: Cardiac implantable electronic devices can detect sleep-disordered breathing (SDB). Few studied the prognostic value of device-detected SDB in cardiovascular risks. We aim to determine the association between device-detected SDB and cardiac events.